Agreement between Wayne State University and the Wayne State University Chapter of the American Association of University Professors, August 1, 1981 to July 31, 1983 - American Association of Univ. Professors, Washington, DC.; American Association of Univ. Professors, Washington, DC.; Wayne State Univ., Detroit, MI. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1981)
The collective bargaining agreement between Wayne State University and the Wayne State University Chapter (1,460 members) of the American Association of University Professors (AAUP) covering the period August 1, 1981-July 31, 1983 is presented. Items covered in the agreement include: AAUP recognition, personnel classification, association rights and privileges, deduction of union dues and fees, past policies, nondiscrimination, no strike/lockout, layoff and recall procedures, participation in union activities, salary adjustments for 1981-1982 and 1982-1983, executive order reduction, salary schedules, recommended salaries for new bargaining unit members, medical and dental insurance, long-term disability income insurance, retirement program, life insurance, voluntary early retirement, vacations, holidays, leaves of absence with/without pay, professional leaves, maternity leaves of absence, fractional-time employees, administration of agreement, grievance procedure, selection advisory committees, validity, duration of agreement and cessation of bargaining, term appointments, tenure and promotion procedures, review of professional duties, personnel files, research awards and educational development grants, department and college by-laws, tuition assistance program, student evaluation of faculty teaching, university-wide committees, budget advisory committees, equal opportunity committee, and transfers between bargaining units. (SW)
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Advisory Committees; Arbitration; Collective Bargaining; College Faculty; Contracts; Employment Practices; Faculty Evaluation; Faculty Promotion; Faculty Workload; Fringe Benefits; Grievance Procedures; Higher Education; Job Layoff; Leaves of Absence; Part Time Faculty; Personnel Policy; State Universities; Teacher Employment Benefits; Teacher Retirement; Teacher Salaries; Tenure; Unions; AAUP Contracts -- Wayne State University MI; American Association of University Professors -- Bylaws -- Faculty Reappointment -- Personnel Files -- Tuition Benefit Programs -- Union Rights; Legal/Legislative/Regulatory Materials